Performance Evaluation Of Insurance Companies Using Data Envelopment Analysis (Studies Empirical On Insurance General Listed On The Indonesian Stock Exchange Period 2020-2023) - Natu, Cecilia Noviaty; Man, Stanis; Seran, Paskalis; Manafe, Henny (SEAN Institute, 2024)
The study analyzes the efficiency levels of general insurance companies listed on the Indonesia Stock Exchange from 2020 to 2023 using the Data Envelopment Analysis (DEA) method, specifically the input-oriented variable return to scale (VRS) model. The study uses total assets and operational expenses as input variables and premium income and claims paid as output variables. The results show that out of the 13 companies sampled, Asuransi Ramayana Tbk achieved optimal technical and scale efficiency with a lambda value of 1 throughout the 2020-2023 period. Other companies reached technical and scale efficiency but were not consistent over the four-year period. Academically, this research contributes to existing literature by adding theories on company performance efficiency using the DEA method in general insurance companies listed on the IDX. Practically, the analysis results provide insights into areas that need improvement by management to enhance efficiency. Thus, this study offers additional insights for various stakeholders to improve the performance and competitiveness of the insurance industry in the future.